2018
DOI: 10.1002/clc.22978
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in sepsis: Comparison of outcomes between patients with demand ischemia, acute myocardial infarction, and neither demand ischemia nor acute myocardial infarction

Abstract: Among patients with sepsis, those with DI had similar adjusted in-hospital mortality compared to those with neither DI nor AMI. Patients with AMI had the highest in-hospital mortality among all groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…This slightly higher mortality rate in our study was likely due to older age, a sicker population, and the presence of delirium. Our results, nevertheless, are consistent with prior studies showing no impact of non-coronary troponin elevation on mortality in patients with septic shock ( 13 , 14 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This slightly higher mortality rate in our study was likely due to older age, a sicker population, and the presence of delirium. Our results, nevertheless, are consistent with prior studies showing no impact of non-coronary troponin elevation on mortality in patients with septic shock ( 13 , 14 ).…”
Section: Discussionsupporting
confidence: 93%
“…The reported in-hospital mortality rates with septic shock and demand ischemia range from 26.9 to 56% ( 13 17 ). The mortality rate in our cohort of critically sick patients with non-cardiogenic shock or respiratory failure requiring mechanical ventilation was 59.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 16 patients on ECMO, 15 died with 94% mortality [12][13][14]. Additionally, the in-hospital mortality is high for patients with sepsis in addition to acute myocardial infarction as compared to patients without infarction (48.3% vs. 17.7%) regardless of COVID-19 infection [15].…”
Section: Discussionmentioning
confidence: 99%
“…When its level increases, it can reflect the increased severity of myocardial injury, with high specificity. [13][14][15] Previous studies have suggested that myocardial injury, as reflected by elevated cardiac troponin levels in plasma, is common in patients with community-acquired pneumonia. [16] The main reason for poor prognosis in patients with severe sepsis is that patients often have cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%